Observation on Landslide Occurrence by the Rise of Groundwater After Prolong Rainfall Event - Khalid N.H.N.; Usman F.; Omar R.C.; Norhisham S.; Razad A.Z.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Disasters; Groundwater; Rain; Topography; Ground water level; Groundwater monitoring; Natural disasters; Prolong rainfall; Rainfall event; Sandy-SILT; Landslides